HUBUNGAN FASILITAS MULTIMEDIA DENGAN PENINGKATAN HASIL BELAJAR SENI BUDAYA SISWA SMP NEGERI 2 PADANG - Ramu Putri Syahrul, Yofi Sandra, S.Pd, M.Pd, Drs. Erwin A, M.Sn (Universitas Negeri Padang, 2013)
The puproses of this study were to detect and to analysis : Connection between Multimedia Facility with the Upgrade of Students Study Result at State Junior School 2 Padang. The technique of sample withdrawal the thing which used is purposive random sampling which is take building on studi result database. The result of this research indicate that multimedia facility is related to significant about the upgrade of students study result with significant degree 0.000 (0.000 < 0.01), in the manner of achievement pearson correlation as big as 0.0547 with significant degree as big as .000 ≤ 0.01 level up at multimedia facility variable. If sig. ≤ 0,05 then ho is acceptance and ha to push away and if sig . > 0,05 then ho to push away ang ha is acceptance, with connection significant correlation at the 0,01 level.